Efektivitas E-Court Sebagai Sarana Penyelesaian Sengketa Di tengah Pandemi Covid-19 Di Indonesia - Yusia Agatha Sihite; Devi Siti Hamzah Marpaung (Widya Yuridika, 2022)
In the era of the industrial revolution 4.0, the process of progressing the digital and computerized era has greatly increased and has affected almost all corners of the world in aspects of human life, where in this case the legal system in the world is also affected by the influence of digitalization. In the legal order affected by this era of digitalization is the practice of law, especially in the area of the judicial environment. Evidence of the digitization process in the judicial world is the introduction of Virtual Civil Courts, where in Indonesia it is known as the E-Court system. The E-court system is a service for registered users where they register online, make payments online, and estimate the payment online, calls are made through electronic channels and technical trials are conducted electronically. Especially in pandemic conditions like this, many countries are experiencing lockdowns that hinder this legal justice system. So that the digitalization system in the pandemic era like this is very beneficial for the ongoing legal justice system that is in force.  During the Covid-19 pandemic, not many know how government regulations in law enforcement through dispute resolution are carried out through the e-court route, where since the Covid-19 pandemic dispute resolution through e-court has increased very significantly. The e-court itself has been regulated in Perma Number 1 of 2019 and (SEMA) Number 1 of 2020, because there are no other regulations governing e-courts, the problem of online trial regulation in Indonesia is almost the same as the American State. This research uses a method of approach that is normative juridical emphasizing the understanding and study of primary legal materials in the form of legal principles.